Immunological pathogenesis of inflammatory bowel disease: focus on tissue resident memory T cells - Hu, Jiayan; Wang, Wenting; Wang, Muyuan; Wu, Chunye; Jiao, Yao; Li, Yitong; Zhang, Wenji; Liang, Chengtao; Lin, Zhengdao; Yu, Yitong; Li, Junxiang; Mao, Tangyou (Frontiers in Immunology, 2025)
Tissue-resident memory T (TRM) cells are a type of tissue-restricted memory T cells with terminal differentiation and a memory function. They exist in mucosal tissues for a long period. In the absence of disease, TRM cells promote essential inflammation, which reinforces the intestinal barrier and prevents bacterial translocation. However, in inflammatory or autoimmune environments, TRM cells are hyperactivated. This heightened activity causes the host to release excessive pro-inflammatory cytokines, resulting in local immune imbalances and damage to the barrier, ultimately leading to tissue lesions. Numbers of studies have shown that TRM cells play a crucial role in the development and progression of inflammatory bowel disease (IBD), suggesting that targeted regulation of TRM cells homeostasis may be an important strategy for treating IBD. Here, we compiled the existing understanding of the role of TRM cells in IBD, with particular emphasis on the associated mechanisms and approaches for targeting TRM cells in IBD treatment. This review will serve as a foundation for a better understanding of IBD development and enhancing the effectiveness of clinical treatments for IBD.